2007
DOI: 10.1136/bjsm.2007.043083
|View full text |Cite
|
Sign up to set email alerts
|

Short-term glucocorticoid intake combined with intense training on performance and hormonal responses

Abstract: Short-term glucocorticoid administration induced a marked improvement in endurance performance. Further studies are needed to determine whether these results obtained in recreational male athletes maintaining a rigorous training schedule are gender-dependent and applicable to elite athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
1
33
1
4
Order By: Relevance
“…In conclusion, the mechanisms by which short‐term administration of glucocorticoids are able to improve exercise performance is not completely understood [52,56,58,64]. However, single, acute doses do not appear to have the same performance‐enhancing effect as systematic short‐term administration, despite having similar alterations in blood hormonal and metabolic parameters.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In conclusion, the mechanisms by which short‐term administration of glucocorticoids are able to improve exercise performance is not completely understood [52,56,58,64]. However, single, acute doses do not appear to have the same performance‐enhancing effect as systematic short‐term administration, despite having similar alterations in blood hormonal and metabolic parameters.…”
Section: Resultsmentioning
confidence: 94%
“…As a consequence glucocorticoids have the potential to be used as ergogenic aids [51]. Table 3 [52][53][54][55][56][57][58][59][60] summaries the current available evidence of the effect of glucocorticoids on exercise performance. In 2 separate studies, Arlettaz et al [52] and Le Panse et al [58] investigated the effects of 7 days of prednisolone administration (oral dose 60 mg/d and 50 mg/d, respectively) on exercise performance during submaximal exercise (time to exhaustion at 70%-75% VO 2max ).…”
Section: Summary Of the Evidence On Performancementioning
confidence: 99%
“…However, a multiple dose of 60 mg prednisolone daily for seven days did increase cycling time to exhaustion in trained males by 28 min (62%), although this performance was not controlled with a baseline measurement [121]. An almost identical study that did include a baseline measurement showed an increase of 91% (50.9 min) in cycling time to exhaustion using the same dosing regimen, combined with intense training in untrained subjects [122]. Although the statistical comparison was made between baseline measurement and post-treatment, and not additionally to the placebo measurements, it seems likely that this is a true effect as there was no change in the placebo treatment.…”
Section: Resultsmentioning
confidence: 99%
“…An extensive review of the scientific literature performed by Duclos (Duclos, 2010b) showed two types of results: studies supporting the hypothesis that there is no relationship between performance and corticosteroid use in humans (negative studies) (Petrides et al, 1997;Marquet et al, 1999;Baume et al, 2008;Kuipers et al, 2008;Arlettaz et al, 2006Arlettaz et al, , 2008, and studies supporting the hypothesis that there are relationships between performance and corticosteroid use in humans (positive studies) (Arlettaz et al, 2007;Collomp et al, 2008;Nordsborg et al, 2008).…”
Section: Glucocorticosteroidsmentioning
confidence: 94%